PENGARUH KEMASAN, KEWAJARAN HARGA DAN BRAND AWARENESS TERHADAP BRAND LOYALTY (STUDI KASUS PADA WISATAWAN NUSANTARA DI KARTIKA SARI BANDUNG) - A. Gima Sugiama; Emmanuel Febiano Sigit Bayu Pambudy (Universitas Kristen Maranatha, 2017)
The competition of pastry business especially in Bandung is in rapid progress. Kartika Sari is one of the popular pastries brand in Bandung. Kartika Sari’s pastry which is start from small medium enterprise has growth and well known by domestic tourist as one of the most wanted pastry in Bandung. One of the reason is because the owner start to apply the marketing elements correctly in their entrepeneurship. In other words, an integration between entrepreneurship and marketing (entrepreneurial marketing) has created an effectiveness in competition. However, the presence of competitors' brands with various packaging, heterogenous prices and different level of brand awareness could potentially affect the brand loyalty of domestic tourist to Kartika Sari’s pastry brand. The purpose of this study is to determine the impact of packaging, price fairness and brand awareness to brand loyalty toward domestic tourist at Kartika Sari Bandung. The grand theory that used for the basis research were packaging, price and brand. The research method was descriptive method with quantitative research that processed by the regression model analysis techniques. The population study was domestic tourist whom were shopping at Kartika Sari Bandung. The technique of collecting data using questionnaires that distributed to a sample of 150 domestic tourist and who meet the eligibility rate of questionnaires was 110. The results showed that the packaging, the price fairness and brand awareness have significant positive impact to brand loyalty whether in parsial or simultanously. It means more quality in packaging tend to increase the brand loyalty of domestic tourist to Kartika Sari, more fairness in price tend to increase the brand loyalty of domestic tourist to Kartika Sari and the higher of brand awarness, result higher brand loyalty.Keywords: packaging, price fairness, brand awareness and brand loyalty